Polymorphisms in Toll-Like receptors genes and their associations with immunological parameters in Plasmodium vivax malaria in the Brazil-French Guiana Border - Ramírez, Aina D. R (2023)
Background: The innate immune response plays an important role during malaria. Toll-like receptors (TLR) are capable of recognizing pathogen molecules. We aimed to evaluate five polymorphisms in TLR-4, TLR-6, and TLR-9 genes and their association with cytokine levels and clinical parameters in malaria from the Brazil-French Guiana border. Methods: A case-control study was conducted in Amapá, Brazil. P. vivax patients and individuals not infected were evaluated. Genotyping of five SNPs was carried out by qPCR. Circulating cytokines were measured by CBA. The MSP-119 IgG antibodies were performed by ELISA. Results: An association between TLR4 A299G with parasitemia was observed. There was an increase for IFN-ɤ, TNF-ɑ, IL-6, and IL-10 in the TLR-4 A299G and T3911, TLR-6 S249P, and TLR-9 1486C/T, SNPs for the studied malarial groups. There were significant findings for the TLR-4 variants A299G and T3911, TLR-9 1237C/T, and 1486C/T. For the reactivity of MSP-119 antibodies levels, no significant results were found in malaria, and control groups. Conclusions: The profile of the immune response observed by polymorphisms in TLRs genes does not seem to be standard for all types of malaria infection around the world. This can depend on the human population and the species of Plasmodium.